Gross Hematuria and Bladder Tumor in a Patient with Advanced Thyroid Papillary Carcinoma - Takao Ando; Yuki Matsuo; Toshiyuki Ikeoka; Kojiro Oba; Yasuyoshi Miyata; Hideki Sakai; Kuniko Abe; Atsushi Kawakami (Case Reports in Endocrinology)
We present a 73-year-old female with advanced thyroid papillary carcinoma who complained of gross hematuria. We found a bladder tumor and considered it the cause of her symptom. Cystoscopic findings of the tumor were unusual, with peri-tumor vessel formation. Pathological examination of the bladder tumor was consistent with metastasis of thyroid papillary carcinoma. Therefore, we identified thyroid carcinoma metastasis to the urinary bladder as the cause of hematuria in our patient. Thyroid carcinoma metastasis to the bladder is extremely rare, but it should be included among differential diagnoses for gross hematuria in patients with a clinical history of thyroid carcinoma.